Kajian Pustaka Teknologi Pembelajaran Daring Pada Kegiatan Lab Kimia - Riva Ismawati; Arif Widiyatmoko; Adi Nur Cahyono (Postgraduate, University of Mataram, 2023)
Chemistry learning is inseparable from lab activities. Strengthening scientific concepts, skills and attitudes go through some experiments. Online learning is a consequence of the Covid 19 pandemic. It is a must option to make sure that students do not lose knowledge and skills causing academic setbacks. Online learning technology does not only aim to convey theoretical materials but also facilitates lab activities. This article tries to identify online learning technology applied to support activities in chemical laboratories and identify the advantages and disadvantages of their applications. This researcher writes this paper based on a review of the literature collected using the ERIC search. There are 17 selected readings reviewed manually. The analysis results show that Zoom meetings, video conferencing platforms, and the DryLab20 network technology are useful for synchronous laboratory learning. Video experiments, simulations, online modules, web-assign, Schoology, formative, Canva, and learning management systems can be used for asynchronous laboratory learning. There is a possibility of combining synchronous-asynchronous laboratory learning programs. Online laboratory learning has advantages in visualizing laboratory activities even though it cannot yet practice the skills acquired in real laboratories. There should be deep considerations regarding the use of online learning technology in laboratories after the pandemic regarding its advantages and disadvantages